Identifying Geographic Areas of Washington, DC, With Increased Potential for Sexual HIV Transmission Among People With HIV With STIs and Concurrent Elevated HIV RNA: Data From the DC Cohort. (18th March 2022) - Byrne, Morgan; Akselrod, Hana; Monroe, Anne K; Horberg, Michael; Lucar, Jose; Castel, Amanda D; Denyer, Rachel; Doshi, Rupali; Secco, Alessandra; Squires, Leah; Schroeter, Stefanie; Benator, Debra
Abstract: Background: The Undetectable = Untransmittable (U = U) campaign advances the goal of ending the HIV epidemic by promoting durable viral suppression and therefore reducing sexual transmission. We used geospatial analysis to assess the potential for sexual HIV transmission by ZIP code of residence in the District of Columbia (DC) using data from the DC Cohort Longitudinal HIV Study (DC Cohort), a city-wide cohort of persons with HIV (PWH). Methods: DC Cohort participants aged ≥13 years were included in the study period between April 1, 2016, and March 31, 2018. Potential for sexual HIV transmission was defined as the proportion of participants with incident sexually transmitted infection (STI; gonorrhea, chlamydia, syphilis) and with HIV RNA ≥200 copies/mL from 9 months before to 3 months after STI diagnosis. We performed geographic information system (GIS) analysis to determine the ZIP codes with the highest potential for sexual HIV transmission. Results: Of 3467 participants, 367 (10.6%) had at least 1 incident STI, with 89.4% residing in 11 of the 20 residential ZIP codes in DC. Of the 367 participants with an incident STI, at least 1 HIV RNA was available for 348 (94.8%). Ninety-seven (27.9%) individuals with an incident STI had HIV RNA ≥200 copies/mL in the defined time window. Of these 97, 66 (68.0%) resided in 5 of the 20 DC ZIP codes. Conclusions: In DC, 5 ZIP codes of residence accounted for the majority of the estimated potential for HIV transmission among participants in the DC Cohort. These results support focused neighborhood-level interventions to help end the HIV epidemic.